The first thousand years a global history of Christianity - Wilken, Robert Louis, 1936- (Yale University Press, 2012)
"How did a community that was largely invisible in the first two centuries of its existence go on to remake the civilizations it inhabited, culturally, politically, and intellectually? Beginning with the life of Jesus, Robert Louis Wilken narrates the dramatic spread and development of Christianity over the first thousand years of its history. Moving through the formation of early institutions, practices, and beliefs to the transformations of the Roman world after the conversion of Constantine, he sheds new light on the subsequent stories of Christianity in the Latin West, the Byzantine and Slavic East, the Middle East, and Central Asia.Through a selected narration of particularly noteworthy persons and events, Wilken demonstrates how the coming of Christianity set in motion one of the most profound revolutions the world has known. This is not a story limited to the West; rather, Christian communities in Ethiopia, Nubia, Armenia, Georgia, Persia, Central Asia, India, and China shaped the course of Christian history. The rise and spread of Islam had a lasting impact on the future of Christianity, and several chapters are devoted to the early experiences of Christians under Muslim rule. Wilken reminds us that the career of Christianity is characterized by decline and attrition as well as by growth and expansion. Ten years in the making and the result of a lifetime of study, this is Robert Louis Wilken's summa, a moving, reflective, and commanding account from a scholar at the height of his powers"--